Vicarious traumatisation in therapists working with victims of violent crime in contemporary South Africa - Lorgat, Nasreen (My University, 2021)
While there is a body of research on vicarious traumatisation that has been conducted on counsellors and therapists conducting trauma intervention in South Africa that had grown over time, there is arguably a gap in existing research in terms of focusing specifically on therapists who work extensively with crime victims. High rates of violent crime in South Africa and the fact that therapists themselves are not immune to victimisation suggest that the impact of this kind of trauma work may be particularly taxing. The current study explored the subjective experiences of therapists who work with victims of violent crime within a contemporary South African context. An exploratory, qualitative study was conducted in which seven participants were interviewed using a semi-structured interview schedule. The following three superordinate themes were identified as salient across all interviews: Impact of Trauma Work, Coping within the Context of Conducting Trauma Therapy, and Contextual Considerations related to Trauma Work. Falling under these three broad themes 11 subordinate themes were identified, including Emotional effects of vicarious exposure, Heightened awareness of crime and related intentional responses, Subjective triggers, Impact on worldview, Setting boundaries, Self-care practices, Finding meaning in the work, Seeking support, The context of crime and trauma in South Africa, The context of personal exposure to crime for therapists, and Technique as a professional context for crime-related trauma therapy. The findings indicate that although participants were not immune to aspects of vicarious traumatisation, they were highly attuned to detecting this kind of risk within themselves and placed considerable weight on support seeking of various kinds, as well as upon good self-care. Although several participants had themselves been affected by crime, they appeared able to continue to find work with crime victims manageable and meaningful. An interesting finding that emerged was that the nature of the therapeutic approach that therapists chose to use in their work appeared to have a substantial bearing on whether or not they found their work to be negatively impactful
A research project submitted in partial fulfilment of the requirements for the degree Master of Arts in Clinical Psychology to the Faculty of Humanities, School of Human and Community Development, University of the Witwatersrand, 2021